Effect of health insurance coverage on labor allocation: Evidence from US farm households - Jeremy M. D'Antoni; Ashok K. Mishra; Aditya R. Khanal (Health Economics Review, 2014)
In the past three decades, farm families have relied on government payments and off-farm income to reduce income risk and increase total household income. Many studies have analyzed the role of government payments; however, little is known about the impact of health insurance coverage on labor allocation. This study builds on previous literature by using copulas to test for dependence in the labor allocation, addressing the importance of fringe benefits to the farm household, and determining how these considerations affect our knowledge of the impact of fringe benefits on off-farm labor. The results indicate that the off-farm hours worked by the operator and spouse are jointly determined; health insurance coverage is an endogenous variable. Using the predicted probability of insurance coverage and joint estimation techniques, we find a positive and highly significant relationship with the hours worked off-farm. Further, we find that both coupled and decoupled payments are negatively correlated with the hours worked off-farm.
Keywords: C34; I13; J12; J22; J38; J43; Q12; Q18; 330; Health insurance coverage; Endogeneity; Copula; Off-farm labor supply; Dependence; Bivariate tobit; Coupled farm programs payments; Decoupled farm program payments